Analisis Konvervasi Energi Pada Unit Heat Recovery Steam Generator dan Unit Boil-Off Gas Kilang PT. Arun - Fadliani Fadliani; Hamdani Hamdani; Ahmad Syuhada (Jurnal Teknik Mesin Unsyiah, 2014)
The result of this analysist of energy conservation activity exposes the performance generated by PT. Arun NGL in the fields of energy conservation and decrease of greenhouse emissions. The implementtion analysist activities assosieted with international initiatives in addressing climate change, and global warming as well as support the implementation of goverment programs of energy conservation programs and the reduction of greenhouse gas emmisions in the industrial sector. All the data presented in this report have been checked carefully, and all sizes are displayed also was referring to an internationally recognized measurement technique in the industry. Thus, the accurancy of the data included in this report both with regards the level of error is small. In addition, all the data loaded can be trusted because it is supported by the documents that existand can be verified by the stakeholders who want to do this. Based on the result of the assessment, energy saving opportunities and reduction of exhaust gas emmisions are available by empowering, improvise and optimize prodution units. Implementation efforts on energy conservation and the utilization of resources has been implementaed since 1997, which was market by the implementation of the project Marine Boil off Gas (MaBOG) take back the exhaust gas at the time of shipment of LNG (800-1,000 M3 LNG). Marine Boil off Gas has recover 1000 m3 of LNG per shipment in 2003, in installation of heat reovery unit 10 steam generator, which utilizes the thermal energy of the stack gas turbines to generate steam, and turn off or not utilize all the conventional boilers.